German police recruits' perception of skill transfer from training to the field. (June 2022) - Staller, Mario S; Koerner, Swen; Heil, Valentina; Abraham, Andrew; Poolton, Jamie
In order optimally to prepare police officers for the demands in the field, police training has to be designed representatively. However, for the German context, there is a scarcity of research investigating to what extent training meets the demands of the field. To fill this gap, the current study examined if police training in Germany meets the field demands of police officers based on the perspective of police recruits. Thirteen recruits from a German police force were interviewed in a semi-structured way to identify possible matches and discrepancies between training and the field. The qualitative were was analysed using content analysis. The results revealed that recruits valued police training very positively because they were able to apply learned skills and tactics in the field. However, results also indicated that: (a) key informational variables present in the field were missing in training, namely chaotic, highly dynamic situations; and (b) police officers need to be adaptable and flexible in the field to cope with the demands. Finally, the results suggested that police training focuses narrowly on dealing with extreme threats, which differs from the experiences recruits had in the field and may have drawbacks because continuously perceiving social situations as threatening and dangerous is a risk factor for aggressive behaviour. Taken together, the current study provides further insights into the wants and needs of recruits in police training.